KEDAH STATE MOSQUE INSTITUTIONS OF ZAKAT GOVERNMENT - Ramli, Nurman Faiz; Jalil, Mohammad Syukri (Jurnal 'Ulwan, 2024)
Zakat is a mandatory obligation for all physically fit Muslims, as it is one of the essential tenets of Islam referred to as the five pillars. Zakat is of great importance in the collective existence. This is because it can improve the overall well-being of persons who need assistance with their daily needs, education, and other relevant areas. Zakat is considered a potent method for alleviating poverty, as it guarantees that the deserving recipients receive their allocated benefits through the collection of zakat. The State Islamic Religious Council oversees the allocation and supervision of these establishments, as Islamic religious matters in Malaysia are under the purview of state authorities as outlined in the Federal Constitution. Accordingly, each state has a zakat board that is accountable for overseeing the collection of zakat. The diverse implications for the collection and allocation of zakat arise from the unique approaches adopted by different states in dealing with zakat-related issues. However, the question at hand is whether this zakat institution can effectively mitigate the poverty problem that affects some segments of the Malaysian people.